A broadcast scheme for vehicle-to-pedestrian safety message dissemination. (November 2017) - Eyobu, Odongo Steven; Joo, Jhihoon; Han, Dong Seog
Ensuring cooperative awareness by periodic message beaconing in vehicular environments is necessary to address pedestrian safety. However, high periodic basic safety message broadcasting in dense vehicular environments makes accessing the communication channel very competitive. Furthermore, high-frequency periodic broadcasting causes fast device energy dissipation which is a key issue for small computing devices used in wireless sensor and mobile communications. Therefore, in order to achieve reliable message dissemination for vehicle-to-pedestrian safety, energy loss minimization mechanisms for pedestrian mobile devices should be developed. This article proposes controlling the number of broadcasts by eliminating periodic safety message broadcasts from pedestrian nodes; these nodes only receive broadcasts from vehicles and then conditionally communicate with the vehicles when safety alerts are raised. When the pedestrian nodes do not receive messages from any vehicle for a specified period, pedestrian nodes broadcast a high-priority message advertising their position. Furthermore, for the pedestrian, adaptive message emission rates and transmission duration are proposed based on defined vehicle-to-pedestrian separation distances. This approach reduces the pedestrian device energy consumption and end-to-end delay and improves the packet delivery ratio compared to the vehicular broadcast approach for safety messages defined in the IEEE 802.11 standard.